2002
DOI: 10.1016/s0002-9440(10)61159-5
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Profiling of Mouse Bladder Inflammatory Responses to LPS, Substance P, and Antigen-Stimulation

Abstract: Inflammatory bladder disorders such as interstitial cystitis (IC) deserve attention since a major problem of the disease is diagnosis. IC affects millions of women and isClinical and animal models of acute and chronic urinary bladder inflammation have provided several lines of evidence suggesting a central role of mast cells, sensory nerves, and neurokinin (NK)-1 receptors. Fundamental work regarding the participation of sensory nerves and mast cells in cystitis provides indirect evidence, such as increased nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

14
111
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(125 citation statements)
references
References 102 publications
14
111
0
Order By: Relevance
“…CB2 receptors were up-regulated in some patients; however, this difference was not statistically significant. Here we confirm previous murine data 25 in humans, showing that ␤2 adrenergic receptor mRNA was significantly higher in BPS patients than in controls.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…CB2 receptors were up-regulated in some patients; however, this difference was not statistically significant. Here we confirm previous murine data 25 in humans, showing that ␤2 adrenergic receptor mRNA was significantly higher in BPS patients than in controls.…”
Section: Discussionsupporting
confidence: 92%
“…20 Such changes are indicative of the pathophysiological processes taking place during the progression of a disease; therefore some of the causative factors of BPS/IC might be elucidated by uncovering a link between the expression of proteins, mediating neurogenic inflammation, bladder contractility and epithelial permeability. Although there are several studies examining gene expression changes during experimentally induced cystitis in animals, [21][22][23][24][25] human data are scarce. In human BPS patients, the molecular markers for bladder permeability and proteoglycan core proteins have been shown to be down-regulated, 26,27 and there was an increased permeability and decreased tight junction formation of bladder epithelial cell monolayers grown from biopsies in patients with BPS/IC, as compared with cells from normal controls.…”
mentioning
confidence: 99%
“…We believe that this study is the first to demonstrate upregulation of CRF in the urinary bladder and specifically in the urothelium and bladder nerve fibers after CYP-induced cystitis. Previous gene profiling studies have demonstrated upregulation of CRF receptor in the urinary bladder in murine models of cystitis (39). We extend these studies by demonstrating upregulation of CRF in both acute and chronic CYPinduced cystitis as well as by demonstration of increased CRF expression in specific urinary bladder tissues (urothelium and nerve fibers).…”
Section: Discussionsupporting
confidence: 64%
“…However, the present studies demonstrate time-and tissue-dependent upregulation of CRF in bladder reflex pathways with CYP-induced cystitis, but whether or not this upregulation has any functional significance remains to be determined. It may be the case that CRF plays different roles in bladder function during development and inflammatory conditions and may be dependent on the presence of mast cells, as previously suggested (39,50). Clearly, additional functional studies are needed to define the role of CRF in normal and inflamed states.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation